Xeroderma Pigmentosum and Bone Marrow Aplasia: A Rare Association - Shanmugasundaram, Sakthisankari; Kumar, Prasanna N; Lakshmi, S Vidhya; Chaitra, V (Indian Journal of Medical and Paediatric Oncology, 2018)
Xeroderma pigmentosum (XP) is a rare autosomal recessive disorder characterized by hypersensitivity to ultraviolet rays and predisposition to cutaneous malignancies. Hematological disorders associated with XP include myelodysplastic syndrome and acute leukemia. We report a 7-year-old child with XP along with squamous cell carcinoma and bone marrow aplasia.
Keywords: Aplastic anemia; pancytopenia; squamous cell carcinoma; xeroderma pigmentosum